Behind Asylum Walls: Studying the Dialectic Between Psychiatrists and Patients at Montreal's Saint-Jean-de-Dieu Hospital during the first half of the Twentieth Century. (8th December 2017) - Perreault, Isabelle; Thifault, Marie-Claude
Summary: Hospital archives contain traces of psychiatric patients' words—written and spoken accounts that could be construed as delusional, irrational and poetic. How are these singular historical narratives, transcripts and letters, which are often out of the ordinary, to be addressed? The historian is tempted to write these psychiatric cases off as nothing more than colourful examples. However, as per French historian Arlette Farge, 'to take this discourse and work with it offers an answer to the desire to reintroduce lives and individualities into the historical narrative'. This paper questions the ways histories of madness are read and written, based on the rare words of patients found in psychiatric archives. How do we analyse these unique traces of intercourse between experts and marginalised individuals? What do they reveal about power relationships or resistance? Which standpoint should be taken, in order to write history from below, given the challenges posed by the narratives and social positions of the actors involved?